Distinctive structural motifs of RNA G-quadruplexes composed of AGG, CGG and UGG trinucleotide repeats - Malgowska, Magdalena (Oxford University Press, 2014)
Trinucleotide repeats are microsatellite sequences that are polymorphic in length. Their expansion in specific genes underlies a number of neurodegenerative disorders. Using ultraviolet-visible, circular dichroism, nuclear magnetic resonance (NMR) spectroscopies and electrospray ionization mass spectrometry, the structural preferences of RNA molecules composed of two and four repeats of AGG, CGG and UGG in the presence of K(+), Na(+) and NH(4)(+) were analysed. (AGG)(2)A, (AGG)(4)A, p(UGG)(2)U and p(UGG)(4)U strongly prefer folding into G-quadruplexes, whereas CGG-containing sequences can adopt different types of structure depending on the cation and on the number of repeats. In particular, the two-repeat CGG sequence folds into a G-quadruplex in potassium buffer. We also found that each G-quadruplex fold is different: A:(G:G:G:G)A hexads were found for (AGG)(2)A, whereas mixed G:C:G:C tetrads and U-tetrads were observed in the NMR spectra of G(CGG)(2)C and p(UGG)(2)U, respectively. Finally, our NMR study highlights the influence of the strand sequence on the structure formed, and the influence of the intracellular environment on the folding. Importantly, we highlight that although potassium ions are prevalent in cells, the structures observed in the HeLa cell extract are not always the same as those prevailing in biophysical studies in the presence of K(+) ions.